Code Switching Usage in 50 First Dates Movie - Lia Nurmalia; Prapti Wigati Purwaningrum (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
The objectives of this research are to know the used of Code-Switching in 50 First Date movie. This research uses a descriptive qualitative method. The final results indicate the three types of code-switching are used in 50 first dates movie, namely tag switching 47.8%, intra-sentential 39.1%, and inter-sentential 13.2%. The most used type is tag switching, it shows that switching done by the character of the movie, Ula, are tag and exclamation. The most reason Ula switches the language is that he wants to change the hearers' perception. They are two reasons for code-switching; metaphorical code-switching 69.6% and situational code-switching 30.4%.Â The function of switching the code is mostly to involve the hearer directly into the conversation. They are five functions of code-switching referential 8.7%, directive 39.1, expressive 34.8%, phatic 13.1%, and metalinguistic 4.3%.